Libraries and copyright holders: is compromise possible? - E. I. Borisova (Библиосфера, 2014)
A debatable issue at the present stage of libraries development is finding a compromise between the public interest in a public library services for Russian citizens and the private interests of rights holders to ensure their intellectual property rights. The purpose of this article is to analyze the changes in the legal regulation of relations arising with the creation and use of products of science, literature and arts and their effect on Russian libraries activity. Federal Law № 72-FZ «On amendments and additions to the Russian Federation law “On copyright and related rights”» (20.07.2004) introduced rules limiting the freedom of libraries to use copyright products, in particular the ban on providing temporary free applying digital copies of publications (including those provided by the mutual use of library resources) outdoor libraries. After the entry into force of the 4th part of the Civil Code of the Russian Federation since 01.01.2008 the library community has consistently defended the need to amend Articles 1273-1275 of the 4th part of the Civil Code of the Russian Federation and to overcome erected legal barriers. The result of six-year struggle was a certain compromise between the interests of libraries and rights holders, made in adopted Federal Law № 35-FZ «On amendments to the first, second and fourth parts of the Civil Code of the Russian Federation and certain legislative acts of the Russian Federation» (12.03.2014). A new version of the 4th part of the Civil Code of the Russian Federation attempted to balance the public interest in accessibility of services provided by the library and the private interest of copyright holders in protecting intellectual property rights, which is one of the can be considered as one of the most pressing challenges of our time - library-copyright confrontation. The author was directly involved in the development of amendments to the 4th part of the Civil Code of the Russian Federation in respect of the libraries activities and their lobbying the process of the Federal Law № 35-FZ discussion and adoption.